162 TRENDS IN EMERGENCY DEPARTMENT USE BY OLDER PEOPLE DURING THE COVID-19 PANDEMIC. (18th November 2021) - Howley, F; Lavan, A; McMahon, G; Mehmood, M; Briggs, R
Abstract: Background: Older people have been disproportionately affected by the COVID-19 pandemic with reports suggesting that many older people deferred seeking healthcare during the pandemic due to fear of contracting COVID-19. The aim of this study was to examine trends of emergency department (ED) use by older people during the first wave of the COVID-19 pandemic compared to previous years. Methods: The study site is a 1, 000-bed university teaching hospital with annual ED new-patient attendance of >50, 000. All ED presentations of patients aged ≥70 years from March–August 2020, 2019 and 2018 inclusive (n = 13, 989) were reviewed and compared for presenting complaint, Manchester Triage Score, and admission/discharge decision. Results: There was a 16% reduction in presentations across the 6 months in 2020 compared to the average of 2018/2019. On average 4 fewer people aged ≥70 years presented to the ED per day in 2020. Much of this was concentrated in March (33% fewer presentations) and April (31% fewer presentations), when the country was in 'lockdown', i.e. non-essential journeys were banned. There was a 20% reduction in patients presenting with stroke and cardiac complaints. In the three months following easing of restrictions, there was a 25% increase in falls and orthopaedic injuries when compared to 2018/2019. Conclusion: This study demonstrates a significant decline in the number of older people presenting to the ED for unscheduled care, including for potentially time-dependent illnesses such as stroke or cardiac complaints. Presenting to the ED remains the most frequent route by which unwell older people access acute hospital care and it is vitally important that they continue to do so in a timely manner when necessary. Given the possibility of further lockdowns and restrictions, this message needs to be communicated to older people clearly by healthcare professionals and governmental bodies to mitigate against adverse outcomes related to delayed or deferred care.